A comparative study of forecasting container throughput through time series analysis - Raman, Siti Nurfaizzah; Sufahani, Suliadi; Ismail, Zuhaimy (Vibus Innovative Publishing Solution, 2017)
This paper shows different techniques used in the operational research to encounter with forecasting the total container throughput handling. Each techniques approached has its objective and constraints regarding to the research problem. The container throughput is responsible for large investments in port infrastructure development as the aims is to established a sufficiently accurate forecasting decision support system since they try to follow the global trends in the optimization of port operations and facilities.